2010
DOI: 10.1103/physrevd.81.124042
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy measures for the algebraic classification of numerical spacetimes

Abstract: We study the issue of algebraic classification of the Weyl curvature tensor, with a particular focus on numerical relativity simulations. The spacetimes of interest in this context, binary black hole mergers, and the ringdowns that follow them, present subtleties in that they are generically, strictly speaking, Type I, but in many regions approximately, in some sense, Type D. To provide meaning to any claims of "approximate" Petrov class, one must define a measure of degeneracy on the space of null rays at a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…They determined the degeneracies between the PNDs by solving the eigenbivector problem and measuring the difference between eigenvalues. Their analysis found that the spacetime first numerically settled to type II, which has only one double PND, and then to type D. Owen [30] later showed that this measure was sensitive to the choice of tetrad used to compute the Weyl scalars needed to solve the characteristic equation. He proposed a new measure, less sensitive to the choice of tetrad, and showed that the spacetime settled to type D without first settling to type II.…”
Section: Overview and Historical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…They determined the degeneracies between the PNDs by solving the eigenbivector problem and measuring the difference between eigenvalues. Their analysis found that the spacetime first numerically settled to type II, which has only one double PND, and then to type D. Owen [30] later showed that this measure was sensitive to the choice of tetrad used to compute the Weyl scalars needed to solve the characteristic equation. He proposed a new measure, less sensitive to the choice of tetrad, and showed that the spacetime settled to type D without first settling to type II.…”
Section: Overview and Historical Backgroundmentioning
confidence: 99%
“…These conditions are formulated in a fully covariant way and thus avoid the complications in [29,30] due to tetrad choice.…”
Section: Overview and Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of a consistent and suitable tetrad for NR continues to be explored [18,19]. Despite the ongoing challenges, a technique for computing the Weyl scalars has been successfully implemented and used for analysis where detailed comparison between waveforms was not necessary [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the first case, the goal is to analyze curvature quantities at finite distances to provide information about the Petrov classification of the spacetime, test properties of perturbed Kerr black holes, probe regimes of strong gravity, etc. [14,[20][21][22][23][24]. In the second case, the goal is to analyze curvature quantities extrapolated or evolved to asymptotic null infinity to compute gravitational waveforms [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%